Tuning Neuromodulation Effects by Orientation Selective Deep Brain Stimulation in the Rat Medial Frontal Cortex - Lehto, Lauri J.; Filip, Pavel; Laakso, Hanne; Sierra, Alejandra; Slopsema, Julia P.; Johnson, Matthew D.; Eberly, Lynn E.; Low, Walter C.; Gröhn, Olli; Tanila, Heikki; Mangia, Silvia; Michaeli, Shalom (Frontiers in Neuroscience, 2018)
Previous studies that focused on treating major depressive disorder with conventional deep brain stimulation (DBS) paradigms produced inconsistent results. In this proof-of-concept preclinical study in rats (n = 8), we used novel paradigms of orientation selective DBS for stimulating the complex circuitry crossing the infralimbic cortex, an area considered analogous to human subgenual cingulate cortex. Using functional MRI at 9.4 T, we monitored whole brain responses to varying the electrical field orientation of DBS within the infralimbic cortex. Substantial alterations of functional MRI responses in the amygdala, a major node connected to the infralimbic cortex implicated in the pathophysiology of depression, were observed. As expected, the activation cluster near the electrode was insensitive to the changes of the stimulation orientation. Hence, our findings substantiate the ability of orientation selective stimulation to recruit neuronal pathways of distinct orientations relative to the position of the electrode, even in complex circuits such as those involved in major depressive disorder. We conclude that orientation selective stimulation is a promising approach for stimulating brain areas that inherently require individualisation of the treatment approach.